Advance Directives: Rethinking Regulation, Autonomy & Healthcare Decision-Making - Chan, Hui Yun (International Library of Ethics, Law, and the New Medicine, 2018)
This book offers a new perspective on advance directives through a combined legal, ethical and philosophical inquiry. In addition to making a significant and novel theoretical contribution to the field, the book has an interdisciplinary and international appeal. The book will help academics, healthcare professionals, legal practitioners and the educated reader to understand the challenges of creating and implementing advance directives, anticipate clinical realities, and preparing advance directives that reflect a higher degree of assurance in terms of implementation.